The impact of the ECB's targeted long-term refinancing operations on banks' lending policies: The role of competition - Desislava C. Andreeva; Miguel García-Posada (European Central Bank (ECB), 2020)
We assess the impact of the Eurosystem's Targeted Long-Term Refinancing Operations (TLTROs) on the lending policies of euro area banks. We first build a theoretical model in which banks compete in the credit and deposit markets. We distinguish between direct and indirect effects. Direct effects take place because bidding banks expand their loan supply due to the lower marginal costs implied by the TLTROs. Indirect effects on non-bidders operate via changes in the competitive environment in banks' credit and deposit markets. We then test these predictions with a sample of 130 banks from 13 countries focusing on the first TLTRO series. Regarding direct effects, we find an easing impact on margins on loans to relatively safe borrowers, but no impact on credit standards. Regarding indirect effects, there is a positive impact on the loan supply on non-bidders which operates via an easing of credit standards.
Keywords: G21; E52; E58; 330; unconventional monetary policy; TLTROs; lending policies; competition